3D‐printed scaffold composites for the stimuli‐induced local delivery of bioactive adjuncts. (6th September 2021) - Bandiera, Antonella; Catanzano, Ovidio; Bertoncin, Paolo; Bergonzi, Carlo; Bettini, Ruggero; Elviri, Lisa
Abstract: Polysaccharide scaffolds have been successfully employed to reconstruct environments that sustain skin tissue regeneration after injuries. Three‐dimensional (3D) advanced additive manufacturing technologies allow creating scaffolds with controlled and reproducible macro‐ and micro‐structure that improve the quality of the restored tissue to favor spontaneous repair. However, when persistent inflammation occurs, the physiological tissue healing capacity is reduced, like in the presence of pathologies like diabetes, vascular diseases, chronic infection, and others. In these circumstances, the bioavailability of therapeutic adjuncts like the growth factors in addition to the standard treatments represents undoubtedly a promising strategy to accelerate the healing of skin lesions. Precisely designed polysaccharide scaffolds obtained by 3D printing represent a robust platform that can be further implemented with the controlled delivery of bioactive adjuncts. Human elastin‐like polypeptides (HELPs) are stimuli‐responsive biopolymers. Their structure allows the integration of domains endowed with biological functionality, making them attractive compounds to prepare composites with smart properties. In the present study, 3D‐printed alginate and chitosan scaffolds were combined with the HELP components. The HELP biopolymer was fused to the epidermal growth factor (EGF) as the bioactive domain. Different constructs were prepared and the stimuli‐responsive behavior as well as the biological activity were evaluated, suggesting that these smart bioactive composites are suitable to realize multifunctional dressings that sustain the local release of therapeutic adjuncts.